Location, Motivation, and Social Capitalization via Enterprise Social Networking. Issue 1 (18th October 2013) - Fulk, Janet; Yuan, Y. Connie
Abstract This article conceptualizes how the affordances of enterprise social networking systems can help reduce three challenges in sharing organizational knowledge. These challenges include location of expertise, motivation to share knowledge, and social capitalization in the form of developing and maintaining social ties with knowledge providers to actualize knowledge sharing. Building on previous theories and empirical research on transactive memory theory, public goods theory, and social capital theories, as well as recent research on enterprise social media, we argue that the affordances of enterprise social networking systems can better address these knowledge sharing challenges than those of conventional knowledge management systems in that social networking applications can blend connective and communal sharing of knowledge.